Descrição diacrônica da presença/ausência do sujeito e das variedades do objeto direto anafórico em jornais catarinenses - Giachin, Amanda e Sá (2016)
This dissertation investigates two phenomena under diachronic generative perspective: the fulfillment/non-fulfillment of the subject and the ways to perform the anaphoric direct object in diachronic texts of Brazilian Portuguese (BP), more specifically in Santa Catarina dialect, in newspaper articles published in periodicals which circulated in the city of Florianópolis (SC). The corpus of the research was composed by twelve newspapers distributed in three phases: (from 1832 to 1850): O Expositor, O Relator Catharinense, O Conciliador Catharinense, O Novo Iris; (from 1897 to 1901): O Estado, A Ideia, Mercantil, Regeneração; (from 1945 to 1950): Diário da Tarde, O Colegial, O Mariano, A Patrulha. The study of the fulfillment of the subject was based on the researches of Duarte (1993;1995), Figueiredo Silva (1996), Barra Ferreira (2000), Rodrigues (2004) and Gravina (2008;2014). It was made a comparison of the change in the status of the null subject observed by these authors and the results of our data in this historical period, in order to observe whether in a formal corpus from Santa Catarina there would be evidence of the change witnessed in previous studies. The study of the direct object was based on the findings of studies such as Duarte (1986), Corrêa (1991), Magalhães (2006), Cyrino (1994) and Macedo Costa (2012), which state that there is an increase in the use of an empty category in the direct object position, while the use of clitics present a decrease in this position. Our objective was to investigate the ways to perform the anaphoric direct object in order to identify whether such a change also would demonstrate in a formal corpus from Santa Catarina. The analysis of data concerning the subject revealed that the use of filling strategies (pronominal subject or anaphoric lexical subject) increases over time. During the 19th century we find the predominant use of null subjects; however, in the first half of the 20th century there is a large increase in filling the subject. Data analyzed with a focus on anaphoric direct object demonstrate the increase in the empty category, corroborating the results of the studies cited above. As Gravina (2008) and Macedo Costa (2012), we find evidence of change in grammar concerning the subject and the direct object in diachrony from a formal corpus, despite its conservative characteristics.